Spatial Modeling for River Quality Assessment to Enhance Sustainable Water Resource Management Regulations - Syafrudin, Syafrudin; Sarminingsih, Anik; Juliani, Henny; Sejati, Anang Wahyu; Budihardjo, Mochamad Arief; Sani, Muhammad Thariq; Wati, Hessy Rahma; A'yun, Husnul Karimah Qurrata (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Water is a crucial asset and serves as a significant factor in the quality of life, especially in supporting key sectors such as agriculture, energy, industry and conservation of natural ecosystems. Water quality can be significantly affected by pollution from effluents, especially in developing countries such as Indonesia which faces the added challenge of rapid population growth. This research focuses on monitoring water quality in the Garang River Sub-region, Semarang, by utilizing Internet of Things (IoT) technology for real-time monitoring. The methods used include the Storm Water Management Model (SWMM) model and an IoT-based monitoring system to measure important parameters such as temperature, pH, turbidity, Dissolved Oxygen (DO), Chemical Oxygen Demand (COD), and nitrate and phosphate concentrations. The results showed that the Chemical Oxygen Demand (COD) parameter often exceeded quality standards, especially in areas with domestic and industrial activities. The IoT monitoring system facilitates precise and instantaneous data gathering., supporting sustainable water resources management. This research emphasizes the need for evaluation and adjustment of policies related to waste management and spatial planning to reduce pollution and improve water quality.